Relational regulation and Chinese real estate investment in London: moving beyond the territorial trap. Issue 2 (17th February 2023) - Raco, Mike; Sun, Yixiang; Brill, Frances
ABSTRACT: National governments, urban authorities and supra-national bodies increasingly see the provision of new housing as a core priority. There has been a strong emphasis on reforming the regulatory environments that exist within geographical territories and making them more welcoming to inward investment. However, such outlooks we claim often fall into a territorial trap and give too much prominence to the regulations and policy environments found in recipient destinations. The paper argues instead for a more recursive focus on the ways in which decisions taken in 'source' and 'host' locations need to be understood as part of a mutually constitutive system of governance. Using the example of Chinese residential investment into London, it argues that investment trends, processes and outcomes reflect a recursive combination of regulatory and political changes in both the city and within China, with the latter becoming increasingly influential. As we show, the Chinese Communist Party has been exerting greater control over the activities of Chinese real estate enterprises and what products are 'permitted' for investment and how this should be done. The paper reflects on the implications for recent academic and policy writings on urban territorial competition.